Beyond changing diapers: stress and decision-making among parents of girls with congenital adrenal hyperplasia seeking consultation about feminizing genital restoration surgery. Issue 6 (December 2019) - Szymanski, Konrad M.; Salama, Amr K.; Whittam, Benjamin; Frady, Heather; Cain, Mark P.; Rink, Richard C.
Summary: Introduction/Background: The impact of having a child with atypical genitalia due to a life-threating chronic medical condition like congenital adrenal hyperplasia (CAH) is poorly understood. Objective: The aim of the study was to determine parental stress and impact of CAH on parental decisions, including decisions regarding female genital restoration surgery (FGRS). Study design: The authors surveyed consecutive parents of girls with CAH ≤3 years presenting at a tertiary referral center for FGRS consultation (2016–2019). The survey was developed by three families of daughters with CAH and six clinicians. Nine potentially stressful past experiences were rated on a 6-point Likert scale ('not at all' to 'extremely' stressful). Overall parental stress and strain (broader negative consequences) were reported using validated instruments (Perceived Stress Scale and Caregiver Strain Questionnaire Short Form, respectively). Impact of CAH on past decisions about childcare, social interactions, and who changes diapers were also assessed. Non-parametric tests were used for analysis. Results: Twenty-nine parents (median age: 32years) of 22 consecutive children participated (Prader 3/4/5: 59.1%/36.4%/4.5%). After the study, 20 girls (90.9%) underwent FGRS at a median age of 8 months. The most stressful experiences were having an adrenal crisis ('very much' stressful), waiting for the CAH diagnosis, and making sense of the diagnosis (both 'quite a bit') (Figure 1). Remaining issues were 'somewhat' stressful. Deciding whether to proceed with FGRS was ranked as the least stressful issue. Overall parental stress was similar to overall stress previously reported by spousal caregivers of stroke or heart failure survivors ( P  ≥ 0.15). Overall parental strain was similar to parents of adolescents receiving mental health counseling ( P  = 0.77). Congenital adrenal hyperplasia impacted decisions about babysitting, daycare, who changed diapers, and choosing a pediatrician ( P  ≤ 0.02), but did not impact parental social interactions ( P  ≥ 0.11). Diapers were typically changed by parents (100.0%) and grandmothers (50.0%). Parents anticipated that some individuals currently not allowed to change diapers would be allowed after FGRS: grandfathers (+18.2%), aunts/uncles (+27.3–32.8%), cousins (+18.2%), and family friends (+45.5%). Discussion: The authors present the first assessment of parental stress with respect to different aspects of care of a daughter with CAH. Larger studies are required to determine if the parental stress associated with these experiences varies over time and how these stressors rank relative to each other through the child's development. Conclusion: Parents experience multiple stressors after having a daughter with CAH. Parental stress surrounding a decision about FGRS appears less severe than events pertaining to the diagnosis and medical management of CAH. Congenital adrenal hyperplasia impacts multiple parental decisions.